2021
DOI: 10.4236/ojas.2021.113031
|View full text |Cite
|
Sign up to set email alerts
|

Intake, Energy Expenditure and Methane Emissions of Grazing Dairy Cows at Two Pre-Grazing Herbage Masses

Abstract: A grazing experiment was undertaken to assess the effects of two levels of herbage mass (HM) on herbage DM intake (DMI), fat and protein corrected milk yield (FPCM), grazing behaviour, energy expenditure (HP), and methane emissions (CH 4 ) of grazing dairy cows in spring. Treatments were a low HM (1447 kg DM/ha; LHM) or a high HM (1859 kg DM/ha; HHM). Pasture was composed mainly of cocksfoot (Dactylis glomerata) and lucerne (Medicago sativa), offered at a daily herbage allowance of 30 kg DM/cow, above 5 cm. Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…For example, in Uruguay, Dini et al [ 61 ] and Oscarberro et al [ 78 ] reported grazing average emission values of 109–177 g CH 4 /day and 140–329 g CH 4 /day for heifers, respectively. For grazing lactating cows, Loza et al [ 79 ] reported values between 353 and 374 g CH 4 /day, while in Argentina, for the same animal category and grazing system, Gere et al [ 76 ] reported values from 157 to 203 g CH 4 /day. Studies in Brazil, for example, those by Maciel et al [ 5 ], Oliveira et al [ 4 ], and Hoffman et al [ 80 ], which measured heifers and steers with forage diets, showed results with a wider range of 80–184 g CH 4 /day.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Uruguay, Dini et al [ 61 ] and Oscarberro et al [ 78 ] reported grazing average emission values of 109–177 g CH 4 /day and 140–329 g CH 4 /day for heifers, respectively. For grazing lactating cows, Loza et al [ 79 ] reported values between 353 and 374 g CH 4 /day, while in Argentina, for the same animal category and grazing system, Gere et al [ 76 ] reported values from 157 to 203 g CH 4 /day. Studies in Brazil, for example, those by Maciel et al [ 5 ], Oliveira et al [ 4 ], and Hoffman et al [ 80 ], which measured heifers and steers with forage diets, showed results with a wider range of 80–184 g CH 4 /day.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of performance and milk content is shown in table 1. Loza et al (2021) found no differences in total enteric CH4 emissions (363 g/d on average) or CH4 emission intensity (18.4 g/kg FPCM on average), and the findings are consistent with previous international Munoz et al (2016); Westberg et al (2001); Zubieta et al (2020). Furthermore, Loza et al (2021) reported an average CH4 emission per unit of the estimated feed intake at 21 g/kg DMI and CH4 emission as a percentage of gross energy intake, which is consistent with previous findings of Dini et al (2021) and Cottle et al (2018), which performed metaanalysis for grazing dairy cows on temperate pastures.…”
Section: Effects Of Dha In Dairy Cattle During Springmentioning
confidence: 99%